Class I malocclusion with anterior crossbite and severe crowding - Daltro Enéas Ritter (Dental Press Editora, 2014)
This article reports the orthodontic diagnosis and treatment planning carried out with a 14-year and 5-month-old female patient with esthetic and functional complaints. She presented an Angle Class I malocclusion, anterior crossbite and severe crowding in both maxillary and mandibular arches, in addition to a lightly concave straight facial profile. Orthodontic treatment did not require extraction. Crossbite was corrected by protrusion of upper teeth, which contributed to alignment and leveling of teeth, in addition to improving the patient's facial profile. The case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as a requirement for the BBO certification.